Impak Daripada Kelewatan Perlaksanaan Projek Kerajaan: Perspektif Kontraktor Gred 7 - Masrom, Md Asrul Nasid; Mohamed, Sulzakimin; Kai Chen, Goh; Sarpin, Norliana (Research in Management of Technology and Business, 2021)
Delays are one of the major problems that often occur in the construction industry. Several factors have been identified in influencing the construction time period during the project life cycle and these factors in turn cause delays in construction. The delays, especially in government projects, are due to contractors who lack technical capabilities, lack of experience and expertise in the construction industry. But this problem still persists and is the subject of debate. This study was conducted to identify the causes of delays in the implementation of government projects and identify the impact of delays in the implementation of government projects from the perspective of contractors. The scope of this study focuses on contractors in Kelantan. Data were collected through an interview session with four experienced G7 grade contractors involved in the construction project. The data analysis used was cotent analysis methods to achieve the objectives. The results showed that the main cause of delays in construction was due to financial problems and the impact of delays was excessive costs, scheduling and reorganization of work. This study is expected to contribute in providing information on the causes of delays and impacts due to delays in the implementation of government projects and can help parties involved in construction projects to take systematic planning in reducing project delays.